IMPLEMENTASI KEADILAN GENDER DI PONDOK PESANTREN SABILURROSYAD KOTA MALANG - Bella Fadhilatus Sanah; Ika Wildah Nafisah; Maulidina Zahrah Mukmina; Satria Adli Cholid; Taufan Adi Prayoga (Jurnal Sosiologi Reflektif, 2021)
Gender equality still becomes a sensitive issue in Islamic educational institutions, especially in pesantren, a traditional Islamic educational institution. There is a strong assumption that in the socio-religious tradition of pesantren, women's subordination still practices widely. However, some pesatren take serious attention to overcome this issue through their daily activities within pesantren. One of which is Pesantren Sabilurrosyad in Malang, East Java. This article aims to elaborate on the realization of gender justice in the pesantren. This research uses a qualitative approach through observation and in-depth interviews with the board members of pesantren, as well as its male and female students. The results showed that the Pesantren Sabilurrosyad had implemented the values of gender justice in their socio-religious activities. The implementation forms include providing opportunities for female students to become head of student association; female students are given freedom to recite the Koran directly to the kyai; and female teachers (ustadzah) are given the opportunity to share in one forum with male students.Kesetaraan gender masih menjadi isu sensitive di lembaga pendidikan Islam, khususnya di pondok pesantren. Terdapat anggapan bahwa dalam tradisi sosial-keagamaan di pesantren  subordinasi perempuan masih terjadi. Hal ini menjadi perhatian bagi beberapa pesantren yang ingin menjadikan isu ini sebagai bagian dari aktivitas pesantren, salah satunya adalah Pondok Pesantren Sabilurrosyad di Malang. Artikel ini bertujuan untuk mengelaborasi perwujudan keadilan gender di pondok tersebut. Penelitian ini menggunakan pendekatan kualitatif melalui observasi dan wawancara mendalam terhadap para pengurus ponpes dan santri putra dan santri putri. Hasil penelitian menunjukkan bahwa pondok pesantren Sabilurrosyad telah mengimplementasikan nilai-nilai keadilan gender dalam tradisi sosial-keagamaan pesantren. Wujud implementasi tersebut diantaranya adalah memberikan kesempatan kepada santri putri untuk menjadi ketua pondok, santri putri diberikan kebebasan untuk mengaji langsung kepada kyai, serta pengajar putri (ustadzah) diberikan peluang untuk bersama 1 (satu) forum dengan santri putra.